Carotenoids and carotenes in the fruits of Cucurbita maxima, C. moschata and C. pepo under the conditions of Northwestern Russia - T. M. Piskunova; T. V. Shelenga; P. V. Ozersky; A. E. Solovyeva (Труды по прикладной ботанике, генетике и селекции)
Cucurbits are among the most valuable vegetable crops widely used for food all over the world, being an important source of carotenoids and carotenes, biologically active substances with antioxidant and other types of activity. Their content largely depends on the Cucurbita species and varietal features. The Cucurbita collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) contains more than 3,000 accessions of five cultivated Cucurbita spp. and serves as the most important source of source material for developing new cultivars in order to expand the range of functional food products. The present research was aimed at studying the content of carotenoids and carotenes in the fruits of Cucurbita maxima Duch., C. pepo L. and C. moschata Duch. ex Poir. grown in Northwestern Russia, which is characterized by a short growing season and a low sum of active temperatures. The performed study revealed significant differences between the Cucurbita species and cultivars in terms of the content of carotenoids, total carotenes and β-carotene. In contrast to C. pepo, the accessions of C. maxima and C. moscato were characterized by a wide range of variation of these characters. A statistically significant effect of the flesh and fruit skin color on the content of carotenoids, carotenes and β-carotene in them was observed (p < 0.001). The minimum amount of carotenoids, carotenes and β-carotene was found in the fruits with light yellow flesh, and the maximum in those with dark orange flesh. Cucurbit fruits with red skin accumulated more target compounds in contrast to the fruits with white skin. The identified Cucurbita accessions with high content of carotenes and carotenoids can be used as valuable source material for breeding cultivars with improved biochemical composition, which can broaden the range of functional food products when grown in the regions with unfavorable conditions for the production of this crop.